Screening of plant endophytic actinomycetes producing chitinase and its antagonistic activity against Sclerotinia sclerotiorum - GAO Xiao-ning; Gulpiye; WANG Mei-ying; HUANG Li-li; TU Xuan; KANG Zhen-sheng (浙江大学学报. 农业与生命科学版)
One hundred and eighty-six endophytic actinomycetes strains isolated from nine kinds of plants were screened for chitinase production by showing the transparent zone on the selective media containing chitin, and a high-yield strain GKSHJA of chitinase isolated from the stem of Polygonatum sibirium was obtained, whose antifungal activity on some common plant pathogens was evaluated by using liquid shake culture. The results showed that strain GKSHJA had high inhibition efficiency not only on Sclerotinia sclerotiorum with 85.4% inhibition rate to mycelial growth, but also on other 10 kinds of phytopathogens. The strain GKSHJA was identified as Streptomyces longisporoflavus based on morphological, physiological and biochemical, and cytochemical characteristics. The medium with initial pH 6, containing 1% floury chitin as carbon source and 0.30% beef extract as nitrogen source, incubated at 32℃ for 6 d with 150 r·min-1, was recommended for chitinase production of the strain GKSHJA.